Application of Multiscale Fiber Optical Sensing Network Based on Brillouin and Fiber Bragg Grating Sensing Techniques on Concrete Structures. (24th October 2012) - Zhao, Xuefeng; Lu, Jie; Han, Ruicong; Kong, Xianglong; Wang, Yanhong; Li, Le
Abstract : The paper reports the application of the distributed optical fiber sensing technology and the FBG sensing technology in bridge strain monitoring; the overall changeable characteristics of the whole structure can be obtained through the distributed optical fiber sensing technology (BOTDA), meanwhile the accurate information of local important parts of the structure can be obtained through the optical fiber Bragg grating sensor (FBG), which can improve the accuracy of the monitoring. FBG sensor has a high sensitivity, but it can only realize the measurement of local discrete points for the quasidistributed sensing. BOTDA can realize the long distance and distributed measurement, but its spatial resolution is not high. FBG and BOTDA were applied together in bridge monitoring in this test, taking full advantage of the distributed BOTDA on the overall strain measurements of the structure, as well as monitoring the key parts by the arrangement of FBG. The combined application of BOTDA and FBG can achieve the overall monitoring from point to line and then to the surface and, therefore, obtain more comprehensive information on the strain of the test structure.